The Method of Constructing a Multidimensional Model for Finding the Values of the Parameters of the Incremental Sheet Forming Process - Kosimov, Nodirbek; Jung, Dong Won; Bhandari, Krishna Singh (Key engineering materials, 2021)
The object of research is geometric models of the process of incremental forming of parts from sheet material. The subject of research is a graphical model for finding the optimal values of the parameters of the forming process based on multidimensional descriptive geometry. The author of the article discusses the main optimizing factors and process parameters. Particular attention was paid to the problems of constructing geometric models for determining the optimizing factors for incremental forming. The research method is a way of constructing a graphical optimization model of the process using the projection drawing of Radishchev for multidimensional space. Mathematical modeling was also applied to check the correctness of the obtained optimal parameters.